1985
DOI: 10.1364/ao.24.003330
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion and length stability of Zerodur in dependence on temperature and time

Abstract: The lengths and the thermal expansion values of the glass ceramic Zerodur show a reversible dependence on the thermal history within two temperature intervals. Typical effects associated with this dependence are, for example, isothermal length changes within and permanent length changes below the temperature intervals. It is assumed that relaxation causes the observed effects. The phenomena in the upper temperature range from 1300C to 300 0 C are related to the MgO content. The reversibility of the relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…The damaged layer thickness can be approximated by assuming all of the radiation effects are confined to one homogeneous region of thickness 4 ). Radlein et al 10 found similar density compaction amounts for both Zerodur and Zerodur-M, the latter a modified composition designed to avoid any high-temperature thermal expansion hysteresis effects 12,13 .…”
Section: Previous Workmentioning
confidence: 99%
“…The damaged layer thickness can be approximated by assuming all of the radiation effects are confined to one homogeneous region of thickness 4 ). Radlein et al 10 found similar density compaction amounts for both Zerodur and Zerodur-M, the latter a modified composition designed to avoid any high-temperature thermal expansion hysteresis effects 12,13 .…”
Section: Previous Workmentioning
confidence: 99%
“…11). A notable discrepancy is seen for the 40 o C measurement, perhaps associated with hysteresis phenomena long recognized for this material 14 …”
Section: Zerodur ® Glass-ceramicmentioning
confidence: 75%
“…See figures 3 and 4. The hysteresis effects in Zerodur were described by Lindig et al [8]. We are looking forward to evaluating Schott's developmental material which may exhibit less hysteresis.…”
Section: Thermal Cyclingmentioning
confidence: 92%